2022
DOI: 10.1186/s40478-022-01452-2
|View full text |Cite
|
Sign up to set email alerts
|

Somatic copy number variant load in neurons of healthy controls and Alzheimer’s disease patients

Abstract: The possible role of somatic copy number variations (CNVs) in Alzheimer’s disease (AD) aetiology has been controversial. Although cytogenetic studies suggested increased CNV loads in AD brains, a recent single-cell whole-genome sequencing (scWGS) experiment, studying frontal cortex brain samples, found no such evidence. Here we readdressed this issue using low-coverage scWGS on pyramidal neurons dissected via both laser capture microdissection (LCM) and fluorescence activated cell sorting (FACS) across five br… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 53 publications
(112 reference statements)
0
6
0
Order By: Relevance
“…As the MAD values we obtained using dMDA were poor, we recalculated MAD after gradually increasing the bin size up to 5 Mb, which improved the values as expected 9 . We also found that MAD can be further improved by removing noise using principal component analysis (see methods) 33 ( Supplementary Fig. 2 ).…”
Section: Resultsmentioning
confidence: 85%
See 3 more Smart Citations
“…As the MAD values we obtained using dMDA were poor, we recalculated MAD after gradually increasing the bin size up to 5 Mb, which improved the values as expected 9 . We also found that MAD can be further improved by removing noise using principal component analysis (see methods) 33 ( Supplementary Fig. 2 ).…”
Section: Resultsmentioning
confidence: 85%
“…We removed these calls from downstream analyses, as they could result from either dry lab/wet lab artifacts or germline mutations. 33,55 Filtering of Ginkgo CNV calls…”
Section: Cnv Calling Using Ginkgomentioning
confidence: 99%
See 2 more Smart Citations
“…Although, based on a large genome scan study, rare CNVs with larger effect sizes do not play an essential role in ALS [ 57 ], investigating copy number variants in ALS might be prosperous. In other neurodegenerative diseases such as Alzheimer’s dementia and Parkinson’s disease the role of copy number variants has been extensively studied with convincing positive results [ 71 , 72 ].…”
Section: Discussionmentioning
confidence: 99%